Theoretical and experimental investigations of lead chalcogenides quantum confined structures for solar cell application - Nur Farha, Shaafi (2021)
Solar cell has gained much attention due to its simple design and similarity to dye sensitized solar cells (DSSC), in which the QCS replaces the dye molecules. The QCSs are able to yield more than one exciton upon absorption of a single photon with sufficient energy, a multiple exciton generation (MEG). Theoretically, MEG could increase the efficiency of a PV device ≥ 60%, however QCSCs could deliver an insignificant PV conversion efficiency (PCE) of only ca. 16.6%. This doctoral research therefore aims to: (i) investigate the effect of energy level alignment of the lowest unoccupied molecular orbital of the fluorophore (LUMOfluorophore), with the conduction band minimum of MOS (CBMMOS) on the electron injection efficiency from the fluorophore to the MOS, (ii) determine the geometry of lead chalcogenides QCS (< their exciton Bohr radius) that would exhibit MEG using ab-initio density functional theory (DFT) calculations, (iii) identify the simulated geometries of lead chalcogenides that could be synthesized using a vacuum thermal evaporator (TE) and (iv) investigate the effect of the addition of activated carbon (AC) on the morphology and optoelectronic properties of the lead sulphide (PbS) fabricated using a vacuum TE, and the electron injection efficiency from the fluorophore to the MOS. The results of the study show that the ideal energy level alignment between LUMOfluorophore (-4.0 eV) and CBMMOS (-4.1 eV) supported an efficient electron injection from the fluorophore to the MOS, with an injection efficiency as high as ca. 97%. The structural geometry of PbS, PbSe and PbTe that exhibit MEG were identified viz., (PbS)40, (PbS)74, (PbS)80, (PbSe)16, (PbSe)30, (PbSe)32, (PbSe)50, (PbSe)74, (PbTe)12, (PbTe)16, (PbTe)44, (PbTe)50 and (PbTe)74 with the size of 3.49 nm, 4.86 nm, 4.58 nm, 2.63 nm, 3.20 nm, 3.29 nm, 4.03 nm, 5.02 nm, 2.52 nm, 2.69 nm, 3.90 nm, 4.16 nm and 4.84 nm respectively. The optoelectronic properties of (PbS)80, (PbSe)30 and (PbTe)50 QCS that were obtained from ab-initio DFT calculations were in good agreement the PbS, PbSe and PbTe thin films; which compared based on the first excitonic peaks of the fabricated thin films (nano-sphere morphology) to the PbS, PbSe and PbTe realistic cluster models, which resulted in similarities of 92.93%, 99.38% and 95.49% respectively. The PbS nano-tubules with a size range of 41-76 nm were yielded after the addition of AC with a specific surface area of 80 m 2/g (AC80). PbS nano-sheets with a size range of 36-95 nm were yielded after the addition of AC with a specific surface area of 650 m2/g (AC650). PbS nano-sheets (size range: 33-63 nm) were yielded after the addition of AC with a specific surface area of 1560 m2/g (AC1560). Optoelectronic properties of the fabricated PbS thin films with the addition of AC80, AC650 and AC1560 were similar to that of the (PbS)80 realistic model; determined based on the positions of the first excitonic peaks, which recorded 90.1%, 96.1% and 92.8% of similarity, respectively. The electron injection efficiencies from PbS-AC80, PbS-AC650 and PbS-AC1560 conjugates to the MOS were determined to be 18.48%, 62.71% and 87.18%, respectively. In conclusion, a PbS thin film possessing a nano-sphere morphology and exhibiting MEG could be fabricated using TE without the addition of AC.